IDENTIFIKASI FAKTOR PENAWARAN WISATA DI DESA KETE KESU’ DAN PALAWA’ , TORAJA UTARA, SULAWESI SELATAN - Saemo Kamoyaki Rumengan; Anita Sitawati Wartaman; Marselinus Nirwan Luru (Universitas Trisakti, 2022)
The cultural wealth of Toraja is a gift for the people of Indonesia because it is one of the cultural treasures of the Indonesian people. For this reason, the presence of traditional villages can preserve the form of buildings and the lifestyle of indigenous peoples. Examples of traditional villages that still exist today are the Kete Kesu’ Traditional Village and the Palawa’ Traditional Village. However, there is a huge disparity in the number of tourists, even though these two tourist villages have great tourism potential. Therefore, the purpose of this study is to find out the factors of tourism offerings in the development of Kete Kesu' tourist village and Palawa' tourist village. The targets in this study are to analyze the tourism supply factors and analyze the comparison of the differences in the availability of tourism offering factors in the tourist village of Kete Kesu’ and the tourist village of Palawa'. The method used in this research is descriptive analysis. The result is that there are many differences in the conditions of the tourism offering factors at the two research locations. The supporting facilities for the Palawa’ Traditional Village tourism are also not as many as the Kete Kesu' traditional village support facilities. In its management, many problems are faced, namely the tourism management institution of the Palawa’ Traditional Village which tends to be more traditional in nature, so that the management system applied is also not well established and not optimal